KETERAMPILAN GURU MENGADAKAN VARIASI PADA PEMBELAJARAN MATEMATIKA SISWA KELAS V SD INPRES PAKKOLOMPO KECAMATAN PARANGLOE - Wiwik Pratiwi Yunus; Sukmawati Sukmawati; Rosleny B (Journal of Social Studies, Arts and Humanities (JSSAH), 2022)
TEACHER SKILLS IN MAKING VARIATIONS IN MATHEMATICS LEARNING FOR CLASS V ELEMENTARY SCHOOL STUDENTS (SD NEGERI PAKKOLOMPO)This study aims to describe variations in teaching styles, variations in the use of media and learning materials, and variations in interaction patterns and activities in Mathematics learning. The research conducted is descriptive qualitative research at SD Inpres Pakkolompo. The subjects in this study were fifth grade teachers, with principal informants and fifth grade students. Data collection techniques were carried out through interviews, observation, and documentation. Test the validity of the data through triangulation of sources, times and methods. Meanwhile, the data analysis technique was using the interactive analysis model of the Milles and Hubberman models which included: data collection, data reduction, data presentation, and drawing conclusions. The results showed that the teacher's skills in carrying out variations in Mathematics learning were 1) Variations in teaching styles including variations in voice through emphasizing important words; focusing attention through speech, gestures and clapping; make a moment of silence with a moment of silence; make contact by directing a holistic view of all students; variations of body movements and expressions through hand movements when writing, head movements, and showing cheerful facial expressions; and changing positions by moving and shifting positions to approach students. 2) Variations in the use of media and learning materials through variations of visual media such as modules, textbooks, or pictures; audio-visual media such as learning videos displayed on laptops, and motor media for building space and utilizing learning materials in the surrounding environment. 3) Variations in interaction patterns and activities, namely interaction patterns with the type of multi-way communication; and a variety of activities in the form of lectures, discussions, questions and answers, providing information through videos, or other media, as well as conducting learning outside the classroom.